PENGATURAN DAN PENGAWASAN SEKTOR JASA KEUANGAN BERDASARKAN UU NO. 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN (OJK) - ALINE FEBRIANY LOILEWEN; TITIN TITAWATI (Universitas Mahasaraswati Mataram, 2020)
This study aims to examine and analyze how the Financial Services Authority (OJK) is regulated based on Law No.21 of 2011 concerning the Financial Services Authority (OJK), and how the functions of the Financial Services Authority (OJK) in providing consumer protection in the financial services sector .This study uses a form of normative legal research, which is research based on written regulations and legislation and various literature related to the issues to be discussed in this study. The Financial Services Authority (OJK) based on Law No.21 of 2011 concerning the Financial Services Authority (OJK) has the task of regulating and supervising several financial service sectors, namely the banking sector, capital market, insurance, pension funds, financing institutions and financial service institutions. other. In the banking sector, OJK has the authority to regulate and supervise bank institutions, bank soundness, prudential aspects, bank inspections. Therefore, the issue of bank establishment licensing and bank business license revocation falls under the authority of OJK. With regard to consumer protection, OJK has the authority to take measures to prevent losses to consumers and the public by providing information and education to the public regarding the financial services sector, services and products.